Más sobre los rostros entre motivos vegetales (nota complementaria) (Estudios humanísticos. Geografía, historia y arte, 1997)
Among the decorative motives of some of the original manuscripts of León, written around 1200, a sequence of hidden faces can be found. This essay continuas with a brief stufy and a catalogue of the main ornaments which show this peculiar motive.